THE GLOBAL MARITIME FULCRUM POLICY IN PROMOTING ECONOMIC GROWTH - Yosua Cahyo Pratomo; Sri Murtiana; Sugeng Suryanto (Antis-Publisher, 2026)
Objective: This study examines the role of the Global Maritime Fulcrum (GMF) policy in promoting Indonesia's economic growth and identifies the challenges and opportunities surrounding its implementation. Method: The study takes a qualitative approach, using a literature review strengthened by a systematic search protocol covering core publications from 2010–2024 drawn from Google Scholar, Garuda, Scopus, and DOAJ, supplemented with official policy documents. Results: The GMF shows signs of contributing positively to the economy: national logistics costs stood at 14.29 percent of GDP in 2022, down sharply from earlier estimates of around 24 percent, and the maritime sector's contribution to GDP is targeted to reach 9.1 percent by 2029. Infrastructure development has strengthened inter-island connectivity, better maritime security has improved the investment climate, and maritime diplomacy has opened new market access. Implementation still faces limited infrastructure, marine environmental degradation, weakening policy momentum during the second administration period, and price disparities that persist owing to low return-cargo volumes. Novelty: The study weighs official policy narratives against critical scholarship and recent policy data within a policy implementation framework, offering a more balanced assessment of the GMF as an instrument of economic growth.